An Analysis of English Language Department Students’ Translation Quality and Error in Translating Scientific Article (SDGs) From Indonesian into English - Muhammad Wira Rizki; Havid Ardi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Translating global sustainability discourses like the Sustainable Development Goals (SDGs) requires highly precise scientific communication, yet research on how student translators navigate such specialized texts remains limited. This study aims to analyze the translation errors and quality of English majors in translating SDGs texts from Indonesian into English. Utilizing a descriptive qualitative design, this research involved 17 second-semester English literature students at Universitas Negeri Padang selected through purposive sampling. Data were collected via a translation test and analyzed using Dulay’s Surface Strategy Taxonomy alongside a percentage formula. The results revealed 120 structural and lexical errors: 15 omissions (12.5%), 52 additions (43.3%), 51 misinformations (42.5%), and 2 misorderings (1.7%). Despite the prominence of addition and misinformation errors, the students' overall translation quality is categorized as good. These findings suggest that while undergraduate students demonstrate stable syntactic positioning, explicit pedagogical interventions are required to curb over-generalization and lexical inaccuracy in policy-oriented translations.